2018
DOI: 10.37358/rc.18.10.6621
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Markers with Predictive Value in Polytrauma Patients with Femoral Fractures

Abstract: Polytrauma represents one of the most challenging aspects of modern medicine, due to its high mortality and morbidity, affecting especially young, active patients. Therefore, research is nowadays directed towards optimising the treatment for these patients, which is extremely difficult, as polytrauma is characterized by a complicated pathophysiology with intricate pathways, potentially generating local and general complications and requiring a multidisciplinary approach. An essential issue for these patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Numerous studies identified a correlation between the presence of anemia, increased mortality and diminishing postoperative functional outcomes in patients with proximal femoral fractures [3,4,13,14]. Identifying the ideal operator time from the perspective of limiting preoperative blood loss should be a constant concern to ensure therapeutic success for patients with trochanteric fractures.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies identified a correlation between the presence of anemia, increased mortality and diminishing postoperative functional outcomes in patients with proximal femoral fractures [3,4,13,14]. Identifying the ideal operator time from the perspective of limiting preoperative blood loss should be a constant concern to ensure therapeutic success for patients with trochanteric fractures.…”
Section: Resultsmentioning
confidence: 99%